Probiotics Lactobacillus reuteri increase levels of β-Defensin1, sIgA and decrease number of Staphylococcus aureus bacteria colonies in vaginal mucosa on puerperal mice model infected with Staphylococcus aureus - Nur Azizah; Umu Qonitun; Tri Yudani Mardining Raras; Sumarno Reto Prawiro (Universitas Muhammadiyah Semarang, 2020)
Puerperal Infection is a bacterial infection in the genitalia and female reproduction system, which cause the highest mortality among women who post give birth in recent years. The causative agent of this infection is Staphylococcus aureus (S. aureus). Alternative therapy using probiotics such as Lactobacillus reuteri was developed to reduce the increasing incidence of antibiotic resistance. This article studies the effect of probiotics L. reuteri increasing β-defensin1 levels, sIgA levels, and decreasing the number of bacteria S. aureus colonies in the vaginal mucosa on puerperal mice model that induced with S. aureus bacteria. Mice BALB/c were used as an animal model and divided into four different groups. The measurement β-defensin1 levels, sIgA levels, and the number of bacteria S. aureus colonies were conducted in one and three days postpartum. Enzyme-Linked Immunosorbent Assay (ELISA) method was to measure performed for β-defensin1 levels, and sIgA levels, Total plate count was used for the quantity of bacteria S. aureus colonies. β-defensin1 and sIgA levels showed a similar pattern and elevated significantly in all treated group compared to control. The highest value was obtained from a group that administered with L. reuteri and induced with S. aureus in all measurements. The levels of β-defensin1 and sIgA in three days postpartum were higher than that day one. The number of S. aureus colonies was lower in the treated group compare that of the positive control. The average number of bacteria in one day postpartum was higher than three days. The administration of L. reuteri and or induction of S. aureus could increase the level of β-defensin1 and sIgA but reduced decrease in the number of bacteria S. aureus colonies/